Factors in perceived technology use that affect customer satisfaction at Suvarnabhumi Airport - รื่นประเสริฐ ชลิดา; ไตรยสุทธิ์ พิชญาภา; มีนคร กนิษฐา; ขวัญเมือง จุฑามาส (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The perception of technology usage that influences passenger satisfaction with services at Suvarnabhumi Airport plays a crucial role in enhancing the quality of airport services in the modern aviation industry. This study aims to examine the level of passengers’ perceptions of technology usage at Suvarnabhumi Airport and to analyze the factors of perceived usefulness, perceived ease of use, social influence, and facilitating conditions that affect passenger satisfaction. The independent variables in this study include perceived usefulness of technology, perceived ease of use, social influence, and facilitating conditions, while the dependent variable is passenger satisfaction with services at Suvarnabhumi Airport. This research employs a quantitative methodology, collecting data from 400 passengers who have used the airport’s services through online questionnaires distributed via platforms such as Line, Facebook, and Instagram. The data were analyzed using descriptive statistics and multiple regression analysis. The results indicate that perceived usefulness, perceived ease of use, social influence, and facilitating conditions all have a statistically significant effect on passenger satisfaction with airport services.